Complex Magnetovariational and Tectonomagnetic Monitoring of Recent Geodynamics in the Western Slope of the Antarctic Peninsula - Maksymchuk, V.Yu.; Chobotok, I.O.; Klymkovych, T.A.; Kuderavets, R.S.; Nakalov, E.F.; Otruba, Y.S. (Ukrainian Antarctic Journal, 2018)
Aim – investigations of effectiveness and information value of tectonomagnetic and magnetic-variations monitoring complex to study the recent geodynamics of Antarctic Peninsula in the location of Akademik Vernadsky station. Methodology. The methodology provides long-term magnetic variations observations on the Akademik Vernadsky station. On the base of observations electromagnetic induction vector components (Wise vector) are processing in the range 2.5—60 min. Series of this parameters temporal variations are developing. Tectonomagnetic observations are performed on the stationary network of observational points on the Antarctic geodynamic polygon and then, tectonomagnetic anomalies (increasing of a local magnetic field among observational epochs-total magnetic field vector module) is defined. The nature of tectonomagnetic anomalies usually is connected with variations of tectonic tensions. Compounding of magnetic variations and tectonomagnetic observations allows to upgrade certainty of tectonophysic interpretation of geophysical and geological data for investigations of Antarctic Peninsula recent geodynamics. Results. The results of tectonomagnetic and magnetic variations observations on the Akademik Vernadsky station in the location of Antarctic tectonomagnetic polygon during 1998—2017 yrs. were analyzed and generalized. Temporal variations of Wise electromagnetic induction vectors and local geomagnetic field variations were investigated. Anomalous effects in tectonomagnetic variations and Wise vectors temporal variations, caused by seismotectonic processes in the region’s lithosphere were defined. Comparative analyses of tectonomagnetic and magnetic variations data was done. Also was justified possibility their complex for monitoring of recent seismotectonic processes in the location of Akademik Vernadsky station. Conclusions. Complex analyses of long-term tectonomagnetic field and magnetic variations parameters on the Akademik Vernadsky station was done. Correlation between tectonomagnetic effects on the Antarctic geodynamic polygon and anomalous effects in Wise vectors temporal series was defined. Such complex of tectonomagnetic and magnetic variations monitoring is organic and allows to obtain reliable information about Antarctic Peninsula geodynamics in connection with seismic and other geophysical methods.